A case of lymphocytic interstitial pneumonia presenting with a ground glass nodule as an initial finding. (2020) - Kawaguchi, Makoto; Nakayama, Masayuki; Bando, Masashi; Hisata, Shu; Mato, Naoko; Suzuki, Takuji; Takemura, Tamiko; Hagiwara, Koichi
Abstract: A 65-year-old woman had a ground glass nodule, which was suspicious for lung cancer, in her right lung S 6 by chest computed tomography. For diagnosis, video-assisted thoracoscopic surgery was performed, and the specimen showed a pathological pattern of lymphocytic interstitial pneumonia (LIP). Four years after surgery, new localized ground glass shadows gradually increased on the base of the lung. However, because she had no respiratory symptoms and had normal respiratory function, she was observed with no medication. Subsequently, no other underlying diseases associated with LIP developed. The ground glass nodule was the initial lesion of LIP.